PERLAKUAN AKUNTANSI SYARIAH PSAK NOMOR 102 PADA BMT UMMAH BANJARMASIN - Hariyanto Hariyanto (Pascasarjana UIN ANTASARI Banjarmasin, 2015)
This study aims to determine the accounting treatment of sharia PSAK 102 on BMT Ummah Banjarmasin. This type of research is the research field (Field Reseach), are qualitative. Retrieving data using interview techniques and documentation. While the analysis using qualitative descriptive analysis with interactive model of Miles and Huberman. Through techniques qualitative descriptive analysis, this study resulted in the finding that the accounting treatment of sharia in BMT Ummah Banjarmasin yet fully adopted PSAK 102, it can be proved the few that still needs to be improved such as the lack of accounting treatment urbun murabaha, the accounting treatment of pieces of early settlement, and not the accounting treatment of fines upon members (customers) who are in arrears.